1998
DOI: 10.1021/bi980244k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Kinetic Mechanism of Escherichia coli Glycinamide Ribonucleotide Transformylase

Abstract: A kinetic scheme is presented for Escherichia coli glycinamide ribonucleotide transformylase (GAR transformylase, EC 2.1.2.2) based on a steady-state and pre-steady-state kinetic analysis of the reaction in both directions employing stopped-flow absorbance and fluorescence spectroscopy. Steady-state parameters showed that kcat for the reverse direction is about 10 times lower than that for the forward direction although the Km values for formyl dideazafolate and dideazafolate or for glycinamide ribonucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…In contrast, our apo (unoccupied GAR site) and ternary complex structures at pH 6.3 (enzyme active) showed essentially identical, ordered structures for this loop. Our binding studies with WT enzyme conducted at pH 8, the pH for maximum activity, showed independent binding for GAR and fDDF, suggesting that folate binding is not a prerequisite for organizing the active site for productive substrate binding and catalysis, which is consistent with our (see above) and other kinetic studies (8,50) which yielded a random sequential kinetic mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, our apo (unoccupied GAR site) and ternary complex structures at pH 6.3 (enzyme active) showed essentially identical, ordered structures for this loop. Our binding studies with WT enzyme conducted at pH 8, the pH for maximum activity, showed independent binding for GAR and fDDF, suggesting that folate binding is not a prerequisite for organizing the active site for productive substrate binding and catalysis, which is consistent with our (see above) and other kinetic studies (8,50) which yielded a random sequential kinetic mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…This strategy, which mimics evolutionary processes of domain swapping, should complement existing strategies of directed evolution (32,33). GAR and fDDF were obtained and kinetic measurements were performed as described (30). Wild-type E. coli PurN was prepared as described by using a pMSW2 vector in MW12 cells (19).…”
Section: Resultsmentioning
confidence: 99%
“…Restriction enzymes were purchased from either New England Biolabs or Promega; T4 DNA ligase, Calf Intestinal Alkaline Phosphatase, DNA polymerase I Klenow fragment, and Polynucleotide Kinase were from New England Biolabs. N 10 -formyl-5,8-dideazafolate (fDDF) was bought from the John Hynes Laboratory and GAR was synthesized as described (5). G-75 resin was from Sigma, Q-Sepharose resin from Amersham Pharmacia, and nickel-nitrilotriacetic acid from Qiagen (Chatsworth, CA).…”
Section: Methodsmentioning
confidence: 99%
“…These two enzymes carry out similar chemistry in catalyzing the transfer of a formyl group from 10-formyltetrahydrofolate to the amino group of the substrates GAR and AICAR to form fGAR and fAICAR. Investigators have invested their efforts in understanding the mechanisms of the two transformylases with the express purpose of rationally designing inhibitors that specifically target them, and in so doing disrupt purine biosynthesis (4)(5)(6)(7)(8). These and other purine enzymes may function in concert as a multienzyme complex, thus providing another target for chemotherapeutic intervention.…”
mentioning
confidence: 99%